Evaluación de parámetros de resistencia al corte en suelos de ladera cubiertos con vetiver (2017)
The slopes are exposed to erosion and weathering processes that impose a loss of strength of the earth materials. Vetiver has the ability to retain soil particles with their tillers and to strengthen the soil with the roots, inducing tensile strength, which manifests itself as an increase in the values ​​of the parameters of resistance to the cut of the ground. The vetiver system poses a particular solution to this problem. Being systematically arranged on the slope, not only increases the superficial vegetation cover, controlling surface erosion processes, but also improves the conditions of stability, influencing the earth materials in depth. This research focused on the study of the influence of roots on soil cut resistance, following the Mohr-Coulomb failure criterion and on the simulation of these conditions based on the stability of the slope. The results obtained show a clear increase of the properties of resistance of the soil and a beneficial effect based on the stability analysis carried out, which allows to conclude that this system is efficient, in terms of the conditions analyzed, for the increase of the properties of soil resistance.